Analysis of the Issues Faced by the Substitute Teachers and an Evaluation of the Practice of Substitute Teaching from the Perspective of School Administrators - Kürşat ÖĞÜLMÜŞ; Nail YILDIRIM; Gülay ASLAN (Elementary Education Online, 2023)
The aim of this paper is to determine the issues and working conditions of substitute teachers and to evaluate the practice of substitute teaching from the perspective of school administrators and substitute teachers. Surveys were completed by 122 substitute teachers, and 85 school directors and assistant directors of the schools in Tokat province of Turkey where the substitute teachers served in 2010–2011 education year. In this descriptive research, qualitative and quantitative research methods were employed. Survey findings were analyzed using the SPSS 17.0 program and content analysis was conducted for the open-ended questions. The study concludes that the substitute teachers are not satisfied with the remuneration and the working conditions and as a result, their commitment to the profession is quite low. According to the managers; substitute teachers’ performance levels are low and they don’t have enough qualifications in terms of teaching profession.